NILAI-NILAI BUDAYA INSTITUSI PEMBENTUK IDENTITAS SMA NEGERI 3 BANJARMASIN - Andra Rizky Yuwono; Agung Eko Budi Waspada; Krishna Hutama (Universitas Trisakti, 2020)
Institution identity is a brief statement of the institution to the public, reflecting institutional values that can be seen from symbols, behavior and communication. The results of initial observations and interviews, SMA Negeri 3 Banjarmasin does not understand their values and identities. The porpose of this research is to understand the cultural values of the institutions that shape the identity of SMA Negeri 3 Banjarmasin. This research uses content analysis and a cultural approach to understanding the values that shape the identity of SMA 3 Banjarmasin and will be carried out at SMA 3 Banjarmasin, data collection will be done by observation, interview and documentation. The results of this study are visually the cultural values of institutions that shape the identity of SMA Negeri 3 Banjarmasin based on the vision of the school, the values are faith and piety, noble character, intelligent, skill, loving the environment. These 5 values are the core of the school culture that can be visually seen in various activities and programs that affect all internal aspects such as behavior, ways of communication, work environment, daily activities of all member of SMA Negeri 3 Banjarmasin, it forms a habit and culture so that it becomes part of the identity of SMA Negeri 3 Banjarmasin.